2004
DOI: 10.1071/mf03126
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and life history of caridean shrimps in regulated lowland rivers in southern Australia

Abstract: Caridean shrimps are an integral component of lowland river ecosystems in south-eastern Australia, but their distributions may be affected by flow alteration. Monthly shrimp samples were collected from slackwaters in three hydrologically distinct sections of the heavily regulated Campaspe River and the less regulated Broken River for three consecutive years. The distributions of Paratya australiensis, Caridina mccullochi and Macrobrachium australiense, along with their life history in river sections with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(63 citation statements)
references
References 30 publications
5
58
0
Order By: Relevance
“…One important limiting factor for distributions is temperature tolerance, which likely defines the range limits of many freshwater fish (Unmack 2001) andCaridina (de Silva andde Silva 1988), and may even be a selective pressure on egg size (Hancock et al 1998). Other local factors that have been suggested as limiting Caridina distributions are hydrography (Richardson et al 2004;Cook et al unpubl. data) and competition with other species (Poff 1997;Richardson et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important limiting factor for distributions is temperature tolerance, which likely defines the range limits of many freshwater fish (Unmack 2001) andCaridina (de Silva andde Silva 1988), and may even be a selective pressure on egg size (Hancock et al 1998). Other local factors that have been suggested as limiting Caridina distributions are hydrography (Richardson et al 2004;Cook et al unpubl. data) and competition with other species (Poff 1997;Richardson et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Other local factors that have been suggested as limiting Caridina distributions are hydrography (Richardson et al 2004;Cook et al unpubl. data) and competition with other species (Poff 1997;Richardson et al 2004). The responses displayed by a particular species to such factors can depend on the scale being investigated (i.e., stream vs. landscape ;Poff 1997;Cook et al unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrological characteristics seem to play an important role in the evolution of life-history traits of caridean shrimps in the Amazon region (Odinetz Collart & Magalhães 1994) as well as in southern Australia (Hancock & Bunn 1997, Richardson et al 2004. One of the primary problems for life in lotic waters is that small organisms may be transported downstream towards estuaries or coastal waters, where salinities may become unfavourably high for most freshwater organisms.…”
Section: Discussionmentioning
confidence: 99%
“…[40] While slackwaters represent only one key habitat within the complexity of natural rivers [Cooper et al, 1997], they are empirically associated with significantly greater numbers of fish, shrimp, and zooplankton than in fast-flowing waters [Bowen et al, 2003;Richardson et al, 2004;Humphries et al, 2006;Nielsen and Watson, 2008] and physically associated with processes such as organic matter retention [Schiemer et al, 2001]. Therefore, it is probable that changes to slackwaters resulting from regulation are likely to influence biota that use slackwaters at some or multiple stages in their life cycle.…”
Section: Impacts Of Regulation On Slackwatersmentioning
confidence: 99%
“…[3] Slackwaters have been found to contain significantly greater numbers of fish, shrimp, and zooplankton than midchannel habitats in lowland rivers [Bowen et al, 2003;Richardson et al, 2004;Nielsen and Watson, 2008;Ning et al, 2010] with an order of magnitude more fish and shrimp observed in one study [Humphries et al, 2006]. They have also been found to provide refuge from excessively high-water velocities, which stress many biota [Schiemer et al, 2001;Maddock et al, 2004] enabling recolonization of the channel following flow recession [Lancaster and Belyea, 1997;Speirs and Gurney, 2001].…”
Section: Introductionmentioning
confidence: 99%